Galpões de triagem: qualificação do espaço por meio de fluxos de produção - Foppa, Felipe (Universidade do Vale do Rio dos Sinos, 2023)
The expansion in solid waste generation is showing accelerated growth due to increased production and societal consumption habits. The legal framework supports research and covers processes related to the management of solid waste in Brazil, with a focus on the National Solid Waste Policy (PNRS). From the perspective of architecture, the aim is to understand the sequence of stages involved in waste management and how they relate to buildings that sort materials from selective collection. The case study development took into account technical documents made available by the federal government, relating them to a list of architectural and technical elements. The objective was to qualitatively analyze the link between the building and the operational flow in three recycling warehouses located in Porto Alegre, Rio Grande do Sul. The study produced a list of criteria, analyzed through a table with a qualitative scale, indicating the potential for improvement in the relationship between space and function. Although the sorting process was similar in the three units studied, the spatial analysis of operational flows highlighted a gap between the spatial arrangement and the operational process, indicating a need to improve the buildings. The methodology proved effective in analyzing multiple units and can potentially serve as a tool for indicating architectural spatial quality and processes in sorting units.
Keywords: Resíduo sólido; Galpão de reciclagem; Triagem; Arquitetura e Urbanismo; Solid waste; Recycling warehouse; Waste sorting; Architecture and Urbanism; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo